Apoptosis and Bcl-2 expression in the livers of patients with steatohepatitis - Ramalho, Rita M. (2015)
Objectives. Apoptosis may play a role in the pathogenesis of alcoholic (ASH) and non-alcoholic steatolhepatitis (NASH). In this study, we investigated the modulation of apoptosis-related liver proteins in steatohepatitis. Methods. Hepatocyte apoptosis was